Diverse Acinetobacter species and Plasmid-Driven spread of carbapenem resistance in pharmaceutical settings in China - Jintao He; Liang Hong; Meijun Song; Yisha Zhang; Wang Zhang; Linghong Zhang; Danyan Zhou; Zhouwei Chen; Yunsong Yu; Huan Chen; Xiaoting Hua (Environment International)
Acinetobacter species have emerged as a significant public health concern due to their remarkable capacity to acquire antimicrobial resistance. Environmental reservoirs play a crucial role in spreading antimicrobial resistance genes and potentially pathogenic bacteria to clinical settings. However, most studies on nonhuman isolates have focused on a limited sample size. Comprehensive population sampling on One Health principles is essential to monitor the antibiotic resistome and virulome in Acinetobacter spp. Here, we identified three carbapenems-resistant Acinetobacter spp. isolates harboring blaNDM-1 and discovered two novel Acinetobacter species in pharmaceutical production environments. A total of 94 Acinetobacter spp. strains were isolated from pharmaceutical production environments across 17 cities in China, forming 17 distinct Acinetobacter clusters comprising two novel species and 15 previously known species. Phylogenetic analysis indicated that Acinetobacter spp. isolated from pharmaceutical settings are predominantly confined to these settings. Genomic analysis revealed 10 specific families of blaCHDL genes in 51 isolates and blaNDM-1 in three isolates. The overall rates of phenotypic resistance to antimicrobials were low among Acinetobacter spp. isolates, with less than 10 % resistance observed for all tested drugs, and only three isolates carrying blaNDM-1 were resistant to carbapenems. The blaNDM-1 gene was located in approximately 49 kb PTU-Pse8 conjugative plasmids with conserved backbones, although plasmid pXH1688-NDM displayed enhanced growth and stability. Two novel Acinetobacter species, A. yuyunsongii sp. nov. and A. chenhuanii sp. nov., were characterized using phenotypic and genomic analyses. Particularly, A. yuyunsongii sp. nov. XH1639 harbors a blaOXA-58-carrying conjugative plasmid and exhibits multidrug-resistant phenotype. Our study advances Acinetobacter taxonomy and underscores the urgency of monitoring the dynamics of Acinetobacter species in environmental sources to implement effective measures to mitigate transmission risks to healthcare facilities.